Efektivitas Teknik Counterpressure Terhadap Intensitas Nyeri Kala 1 Fase Aktif Persalinan Normal - Nurussa’adah, Awwaliyah; Zulliati, Zulliati; Hidayah, Nurul (Institut Nalanda, 2024)
Pain in childbirth is common and is a process that involves the physiological and psychological mother. Efforts to reduce copycat pain with complementary techniques, one of which is by massase or touch. The purpose of the study was to analyze the effectiveness of the Counterpressure technique in reducing pain in labor during the active phase I in the delivery room of RSUD H. Badaruddin Kasim. This research method is a quasi-experimental research with a Two-Group Postest Only design. The population is all normal maternity mothers when 1 phase is active in January 2023. The samples were maternity mothers who were given counterpressure techniques as many as 10 respondents and maternity mothers who were not given counterpressure techniques as many as 10 respondents with sampling techniques with purposive sampling. Data analysis techniques with the Mann Withney test. The results showed the intensity of maternity pain during the active phase I given counterpressure techniques showed the majority of mild pain by 10 respondents (100%). The intensity of maternal pain during the active phase I that was not given counterpressure techniques showed the majority of moderate pain of 8 respondents (80%).